2023
DOI: 10.1021/acs.est.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Interlayered Interface of a Thin Film Composite Janus Membrane for Sieving Volatile Substances in Membrane Distillation

Abstract: Hypersaline wastewater treatment using membrane distillation (MD) has gained significant attention due to its ability to completely reject nonvolatile substances. However, a critical limitation of current MD membranes is their inability to intercept volatile substances owing to their large membrane pores. Additionally, the strong interaction between volatile substances and MD membranes underwater tends to cause membrane wetting. To overcome these challenges, we developed a dual-layer thin film composite (TFC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Clearly, all the hydrogel composite membranes exhibited a higher LEP than the unmodified PTFE membrane, as shown in Figure f. According to the Young–Laplace equation, the elevation in LEP can be attributed to the relatively dense hydrogel layer and the noninvasive PTFE substrate.…”
Section: Design and Characterization Of The Hydrogel Composite Pmd Me...mentioning
confidence: 88%
“…Clearly, all the hydrogel composite membranes exhibited a higher LEP than the unmodified PTFE membrane, as shown in Figure f. According to the Young–Laplace equation, the elevation in LEP can be attributed to the relatively dense hydrogel layer and the noninvasive PTFE substrate.…”
Section: Design and Characterization Of The Hydrogel Composite Pmd Me...mentioning
confidence: 88%
“…Moreover, compared to the substrate, the GO/PP 5/4 membrane also exhibited high rejection efficiency of other typical volatiles (Figure F) and mixture volatiles (Figure S17). Yet, the slight difference in rejection efficiency depended on the physical properties of the volatiles, including volatility, boiling point, and molecular size …”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to MD’s limitations in rejecting volatiles, traditional hydrophobic macroporous distillation membranes face significant challenges in treating complex hypersaline wastewater. , Lee and Straub recently reported that MD has less than 80% rejection for semi-volatiles with Henry’s constants between 10 –4 and 3 × 10 3 Pa L mol –1 while less than 54% rejection for volatiles with Henry’s constants exceeding 3 × 10 3 Pa L mol –1 . , This is because volatiles can evaporate alongside water and permeate through the hydrophobic macroporous membrane to the permeate side . While pretreatment methods like activated carbon adsorption, catalytic oxidation, or combined separation processes such as RO or nanofiltration (NF) can somewhat treat volatiles, the diverse composition, low concentration, and large fluctuations of volatiles make direct absorption or mineralization inefficient and costly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the issue of trace volatiles in seawater or hypersaline wastewater, photocatalysis can couple with the photothermal process and has the potential as a volatiles removal strategy. Wang et al found that efficient degradation of tetracycline hydrochloride is achievable with sandwich-type absorbers, facilitated by photocatalytic oxidation on the evaporator’s top layer . However, the local high temperature of the evaporation interface often results in volatiles not being completely degraded before they evaporate to the distilled side, particularly the porous membrane evaporator. , Alternatively, the construction of three-dimensional (3D) multifunction nanofiber aerogel evaporators has emerged as a potential solution for simultaneously alleviating salt crystallization and volatile evaporation into distilled water. , In the 3D nanofibrous aerogel evaporator, salt can be moved from the evaporation interface to the bulk water via the interconnecting pores among the nanofibrous matrix. ,, Simultaneously, they can provide numerous adsorption and light-accessible reactive sites for volatile removal, thus facilitating cleaner water production, as demonstrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%